2015
DOI: 10.5194/acp-15-10093-2015
|View full text |Cite
|
Sign up to set email alerts
|

Impact of climate and land cover changes on tropospheric ozone air quality and public health in East Asia between 1980 and 2010

Abstract: Understanding how historical climate and land cover changes have affected tropospheric ozone in East Asia would help constrain the large uncertainties associated with future East Asian air quality projections. We perform a series of simulations using a global chemical transport model driven by assimilated meteorological data and a suite of land cover and land use data to examine the public health effects associated with changes in climate, land cover, land use, and anthropogenic emissions between the 5-year pe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
0
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 64 publications
(56 citation statements)
references
References 50 publications
(54 reference statements)
3
52
0
1
Order By: Relevance
“…Future trends of tropospheric ozone strongly depend on the emission factors of the corresponding precursor compounds (i.e. VOC and NO x ) and indirectly also on land cover and character-istics of the vegetation (Dentener et al, 2006;IPCC, 2013;Fu and Tai, 2015). Some recent studies revealed a stabilization or even a lowering of the tropospheric background ozone concentrations in parts of the industrialized western countries since the turn of the millennium (Logan et al, 2012;Parrish et al, 2012;Oltmans et al, 2013;IPCC, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Future trends of tropospheric ozone strongly depend on the emission factors of the corresponding precursor compounds (i.e. VOC and NO x ) and indirectly also on land cover and character-istics of the vegetation (Dentener et al, 2006;IPCC, 2013;Fu and Tai, 2015). Some recent studies revealed a stabilization or even a lowering of the tropospheric background ozone concentrations in parts of the industrialized western countries since the turn of the millennium (Logan et al, 2012;Parrish et al, 2012;Oltmans et al, 2013;IPCC, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The 20-year climate change has led to large changes in the seasonal mean surface ozone concentration (±10 ppbv), mainly driven by changes in temperature and other meteorological variables, while the historical land use change induces decreases of summer mean surface ozone by up to 5-7 ppbv in the Northern Hemisphere due to deforestation and cropland expansion as discussed in recent studies (Fu and Tai, 2015;Heald and Geddes, 2016). Compared with those changes, we find that the influences of anthropogenic nitrogen deposition can be comparable at regional scales.…”
Section: Discussionmentioning
confidence: 99%
“…As listed in Table 2, we conduct the GEOSChem simulations by using the 1986-1990 MERRA fields (for comparison with the 2006-2010 fields) or the preindustrial land use data (1860 vs. the present-day condition for 2000), generally following the previous work of Fu and Tai (2015) and Heald and Geddes (2016). The impacts of climate change on wildfire emissions (Yue et al, 2015) are not considered here.…”
Section: Asynchronous Coupling and Model Experimentsmentioning
confidence: 99%
See 2 more Smart Citations